PENGARUH MARKET ORIENTATION TERHADAP PURCHASE BEHAVIOUR MELALUI CUSTOMER VALUE DAN PERCEIVED SERVICE SERVICE QUALITY SEBAGAI VARIABEL INTERVENING PADA MALL UPPER CLASS DI SURABAYA - Amelia Angeline Gunawarman (Jurnal Strategi Pemasaran, 2016)
This study aimed to analyze the effect of Market Orientation on Purchase Behavior by Customer Value and Perceived Service Quality as an intervening variable in the upper clas mall in Surabaya. This study will be conducted by distributing questionnaires to 160 respondents consumers who've been to the mall Ciputra World, Galaxy Mall, Grand City, and Tunjungan Plaza minimum of 5x in a single month. Analysis technique used is quantitative analysis techniques with methods of path analysis. The results of this study indicate that Market Orientation affect positively and significantly to Purchase Behavior, Customer Value influence positively and significantly to Purchase Behavior, Perceived Service Quality influence positively and significantly to Purchase Behaviour.